Free-radical scavenging capacity and reducing power of wild edible mushrooms from northeast Portugal: individual cap and stipe activity - Ferreira, Isabel C.F.R. (2007)
The antioxidant properties of two wild edible mushroom species from the northeast of Portugal, Lactarius deliciosus (L.) Gray and Tricholoma portentosum (Fr.) Que´l., were evaluated. Methanolic extracts from the entire mushroom, the cap and the stipe, separately, were screened for their reducing power and free radical scavenging capacity by chemical assays. The total phenolic content was determined, in order to assess its effect on the extract’s antioxidant activity. Both two species showed antioxidant potential; but L. deliciosus proved to be more active. The portion of the mushroom used had an influence on the results obtained, with the cap methanolic extracts exhibiting the greatest antioxidant effect.